Young People in Physical Education and Sports Characteristics of Education Physical Education and Sports - Islombaevich, Sultanov Alisher (European Journal of Life Safety and Stability (2660-9630), 2022)
The article analyzes the need for young people to engage in regular physical education and sports, the specifics of physical education and sports. Thoughts on the priorities aimed at attracting young people to physical culture and sports were highlighted.